Bilateral Syphilitic Optic Neuropathy with Secondary Autoimmune Optic Neuropathy and Poor Visual Outcome - Tanya Kowalski; Dujon Fuzzard; Isla Williams; Jonathan Darby; Heather Gwen Mack (Case Reports in Ophthalmology, 2019)
We describe the case of a 65-year-old man who suffered progressive visual loss despite appropriate treatment of ocular syphilis. Our patient initially presented with a unilateral 6th nerve palsy and associated double vision, which self-resolved over 6 months. His ophthalmic examination was otherwise normal. 12 months after the initial complaint, he represented with dyschromatopsia, reduced visual acuity, tonic pupils, and optic nerve atrophy. He tested positive for syphilis and was admitted for treatment of neurosyphilis with high-dose benzylpenicillin. Despite treatment, at a 4-month review his visual acuity remained poor and progression of optic nerve atrophy was noted alongside the development of bilateral central scotomas. Further testing was congruent with a diagnosis of autoimmune optic retinopathy. We propose this to be secondary to his syphilitic infection. Syphilis is known as the “great mimicker,” and despite being quite treatable, this case highlights ongoing complexity in the diagnosis and management of syphilis, unfortunately with a poor visual outcome.